GANDHI’S “SATYAGRAHA” AND EUROPEAN POSTMODERN REVOLUTIONS - Gajic, Aleksandar; Despotović, Ljubiša (Serbian political thought, 2025)
This paper starts with the comparison between Indian and European civilizations as the “ideal type” personifications of East and West and then turns its attention to their views toward the civil resistance manifestations in cases of illegitimate or unjust rule. By giving a brief review of the birth of the “Indian Independence Movement” with Gandhi's place in it, the paper observes the formation of Gandhi's concept of “Satyagraha” (“Insistence on Truth”). “Satyagraha” was not just a form of non-violent civil resistance as it is known in the West, but moreover, its contrast and overcoming by turning (with some modifications) to Indian religious tradition. By observing “Satyagraha” primarily as an ascetic-religious achievement that leads from “inner-self” toward a social change, this work studies its connection with two other India's traditional praxis – brahmacharya and ahimsa. In the second part of the paper, the phenomenon of “Color Revolution” as a type of non-violent revolution in East Europe is elaborately observed: all of its major forms, strategic and tactical characteristics, and phases of realizations are carefully cognized. Then, in the final part of the paper, Gandhi’s “Satyagraha” and “Color Revolutions” (based on the theoretical and practical recommendations of Gene Sharp) are compared. This comparison gives us a clear contrast between these two forms of civil resistance: the first one that turns to tradition intertwined with spirituality and which leads towards the liberation from colonial submission, and the second one that is profane, anti-spiritual, and inevitably leads to neo-colonial enslavement.
Keywords: India; Europe; Gandhi; Satyagraha; Color Revolutions; tradition; postmodernism